INNOVATION OF TECHNOLOGY TO PRODUCE HIGH QUALITY SALT IN MADEGAN-MADURA - Dharmayanti, Arynta; Ridha, Fuji; Wijiyanti, Rika; Rachmat, Arif; Nusbangga, Dipta; Kurniawan, Fredy (Program Kreativitas Mahasiswa - Teknologi, 2014)
Salt farmers have a problem about the low selling price of salt in common, which is Rp 400,-/kg for B quality salt and Rp 550,-/kg for quality salt A. The cause of the low selling price is because the yield of salt mixed impurities from mineral in soil. In addition, other barriers experienced by the salt farmers are can not operate during the rainy season. It is caused due to the use of the conventional method is not maximized so it produces salt with low quality and quantity. These conditions have been experienced by salt farmers in the Madegan village. Therefore the purpose of the PKM-T is to make the tool named âTalang Cerdasâ producing high quality salt with crystallization method using stainless steel gutters and lenses as a focus rays. The methods used are literature studies and field observations on a group of salt farmers in Madegan village as a partners of salt producers using âTalang Cerdasâ. Then, we made the design and manufacture of equipment. âTalang Cerdasâ has three parts. The first part is tank and pump as a container and pump sea water into it. The second part is the gutters and supporting tools as a medium of salt farmers. The third part is the lens for the convergence process. After that, we did test to the tool and the salt result, and also socialiszation to the salt farmers. âTalang Cerdasâproduces a greater salt that is 2,67 kg/m2 in 14 days which operates for 7 hours per day. Based on the chemical test, the salt has low water content which is 0,733%, the levels of NaCl, Mg, Ca and SO4 respectively 95,73%, 0,05%, 0,08% and 0,17%.Keywords : Salt, stainless steel, crystallization, saltpond